Patients With Super Obesity Do Not Perceive Themselves as Being at Higher Risk for a More Severe Course of COVID-19 Infection - Schäffeler, Norbert; Lohmiller, Jacqueline; Mack, Isabelle; Archid, Rami; Zipfel, Stephan; Stengel, Andreas (Frontiers in Psychiatry, 2022)
Background The coronavirus disease 2019 (COVID-19) pandemic has led to major health-related concerns in the population. Several risk factors for a severe course of COVID-19 disease have been identified, with obesity taking an important role. However, it is unclear whether this association is only known in the expert world or whether individuals also experience themselves as risk patients due to their obesity and whether the desire for weight reduction may also be associated with a hoped-for risk reduction. These questions were addressed in a cross-sectional study of patients who have presented to an obesity center in order to lose body weight. Methods Patients (n=155) of the obesity center were asked to complete an ad hoc questionnaire to assess whether the desire to lose weight is also associated with a hoped-for risk reduction with respect to COVID-19 disease during the middle of the pandemic in the period between October 2020 to April 2021. We additionally assessed their perceived general stress using the Perceived Stress Questionnaire (PSQ). Results In our explorative study, overall worries correlated significantly with worries about contracting COVID-19 (r=.483, p<.001). There has been an association with concerns about severe COVID-19 progression and psychological distress from the COVID-19 pandemic (r=.543, p<.001). In addition, a correlation was found between persons who worry about contracting COVID-19 and feeling like an at-risk patient (r=.530, p<.001). Interestingly, the higher the BMI (>50kg/m²), the lower were the worries in PSQ (ANOVA p=.046). However, COVID-19-related worry was nonetheless present in the higher BMI subgroups. The most intense worries were experienced by individuals with a BMI between 35 and 39 (PSQ worries 50.44), immediately followed by individuals with a BMI between 40 and 49 (PSQ worries 49.36). Discussion & Conclusion An increased risk for a more severe course of COVID-19 infection is not generally perceived by obese individuals. Especially individuals with very high BMI (>50) – although being at very high risk for a severe course of the COVID-19 disease – do not display increased worries which might point towards heightened denial.